2006
DOI: 10.1073/pnas.0600241103
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide rescues ischemic lungs by interrupting MAPK-driven expression of early growth response 1 gene and its downstream target genes

Abstract: Carbon monoxide (CO), an endogenous cytoprotective product of heme oxygenase type-1 regulates target thrombotic and inflammatory genes in ischemic stress. Regulation of the gene encoding early growth response 1 (Egr-1), a potent transcriptional activator of deleterious thrombotic and inflammatory cascades, may govern CO-mediated ischemic lung protection. The exact signaling mechanisms underlying CO-mediated cytoprotection are not well understood. In this study we tested the hypothesis that inhibition of mitoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 35 publications
(45 reference statements)
2
92
0
Order By: Relevance
“…It has been reported that ERK 1/2 also regulates the activation of EGR-1. 33 Here we found that EGR-1 could also provide positive feedback to regulate Ras activation through its target gene GGPPS under CSE . The cells were then lysed and separated into membrane (P100) and cytosolic (S100) portions and subjected to immunoprecipitation and Western blotting against K-Ras and glyceraldehydes-3-phosphate dehydrogenase (GADPH), which was used to show that the separation of membrane and cytosol was successful.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been reported that ERK 1/2 also regulates the activation of EGR-1. 33 Here we found that EGR-1 could also provide positive feedback to regulate Ras activation through its target gene GGPPS under CSE . The cells were then lysed and separated into membrane (P100) and cytosolic (S100) portions and subjected to immunoprecipitation and Western blotting against K-Ras and glyceraldehydes-3-phosphate dehydrogenase (GADPH), which was used to show that the separation of membrane and cytosol was successful.…”
Section: Discussionmentioning
confidence: 67%
“…[33][34][35][36][37][38] We have suggested that EGR-1 can also stimulate HSP70 elevation in an ERK 1/2-dependent manner, which is thought to regulate cigarette smoke-induced inflammatory processes. 18 Here we provide the first evidence that EGR-1 could activate MAPK ERK 1/2 in a positive feedback manner through increasing Ras prenylation by promoting GGPPS transcription in lung epithelial cells during CSE challenge (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…; it has also been reported that carbon monoxide (CO) suppresses the pathogenesis of experimental cerebral malaria 45 . While pleiotropic mechanisms may explain the action of these gazes 45 47 48, it is documented that NO negatively modulates endothelium activation and platelet function 52 whereas CO inhibits the expression of pro-inflammatory genes (e.g., TF and TNF-α) and prevents inflammatory events in vivo 53 . Finally, the finding that TF is potentially a crucial mediator of malaria pathogenesis suggests that therapeutics targeting TF and/or EC 54 could be useful in the treatment of malaria and/or its complications 4,55 .…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of inhibitors were determined by referring to previous in vitro studies that used cultured cells (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Methodsmentioning
confidence: 99%